Legal Framework for Mergers and Acquisitions in India - Srinivas, K. (Prabandhan: Indian Journal of Management, 2009)
Companies Come and Go, Chief Executives Rise and Fall, Industry Sectors Wax and Wane, but an outstanding feature of the past decade has been the rise of business combinations, which may take forms of mergers, acquisitions, amalgamations and takeovers, which are the important features of corporate structural changes. A merger is said to occur when two or more companies combine into one company. One or more companies may merge with an existing company or they may merge to form a new company. This paper aims to analyze the ways of Amalgamation, Merger or Amalgamation under Sections 391 to 394 of the Companies Act, 1956, to analyze the procedure of amalgamation of companies by Central Government and to analyze the mergers in India in general and to analyze the impact of Indian Competition Law on Mergers. This paper is useful for understanding the legal procedure for mergers and acquisitions in India.